Knowledge and Attitude on Organ Donation among Nursing Students of a College in Biratnagar - Limbu, Binu (Europasian Journal of Medical Sciences, 2019)
Introduction: Organ transplantation is an effective therapy for end-stage organ failure. However, there is a large gap between the need for and the supply of donor organs. Nurses have a major role to play in tackling organ and tissue shortages. The main objective of the study was to assess the level of knowledge and attitude on organ donation among nursing students at Biratnagar. Methodology: Descriptive cross-sectional study design among Post Basic Bachelor in Nursing (PBBN) students was carried out in Birat Health College, Biratnagar. A census method using a self-administered semi-structured questionnaire was used for the data collection in 113 respondents. Descriptive statistics i.e., mean, median and standard deviation was used to assess the level of knowledge. Inferential statistics i.e., Chi-square test was used to find out the association between level of knowledge and attitude on organ donation with selected demographic variables. The findings of the study showed that out of 113 respondents, the mean age of respondents was 24.41 years. Similarly, 32.7% of the respondents were from 1st year, 33.6% from 2nd year and 33.6% from 3rd year. More than half, (60%) of the respondents were Brahmin/Chhetri. Similarly, (68.1%) had heard about organ donation from colleagues. Among the studied respondents, (69.9%) had average knowledge of organ donation and almost all (99.1%) of respondents possessed a positive attitude on organ donation. Conclusion: The majority of the respondents had an average level of knowledge and a positive attitude regarding organ donation. The level of knowledge was associated with ethnicity rather than other socio-demographic variables.